Leaders of the Anglo-Saxon Church: from Bede to Stigand - Rumble, Alexander R. (Publications of the Manchester Centre for Anglo-Saxon Studies, 2012)
Essays bring out the important and complex roles played by Anglo-Saxon churchmen, including Bede and lesser-known figures